2012
DOI: 10.1007/s12471-012-0306-6
|View full text |Cite
|
Sign up to set email alerts
|

CT fractional flow reserve: the next level in non-invasive cardiac imaging

Abstract: The haemodynamic effect of a coronary artery stenosis is a better predictor of prognosis than anatomical lumen obstruction. Until recently, no individual noninvasive test could provide both accurate coronary anatomy and lesion-specific myocardial ischaemia. However, computer tomography (CT) fractional flow reserve, which can be calculated from a standard CT coronary angiogram, was recently demonstrated to accurately detect and rule out the haemodynamic significance of individual coronary artery stenoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…However, without automated image processing, TAG remains a time-consuming method [22]. Two recent multicenter trials used computational fluid dynamics to estimate lesion-specific FFR [7,9,23] by calculating the ratio of coronary pressure and mean aortic pressure. It was demonstrated that non-invasive FFR measurement was superior to cCTA for diagnosing ischemic lesions [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, without automated image processing, TAG remains a time-consuming method [22]. Two recent multicenter trials used computational fluid dynamics to estimate lesion-specific FFR [7,9,23] by calculating the ratio of coronary pressure and mean aortic pressure. It was demonstrated that non-invasive FFR measurement was superior to cCTA for diagnosing ischemic lesions [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although CCS is proven to be a valuable tool to detect coronary calcification, it is unable to differentiate media calcification, which is common in patients with CKD, from intima calcification. Moreover, whether the use of computed tomography fractional flow reserve will provide additional diagnostic information in patients with CKD would require further studies [27]. …”
Section: Limitationmentioning
confidence: 99%
“…This is achieved by simulating coronary blood flow using computational fluid dynamics (CFD) based on lumen geometry extracted from CCTA. Latest studies show that CFD provides a better accuracy in identifying ischemia-causing stenoses than the anatomical grade [8]. Both grading and CFD heavily depend on the accuracy of the extracted coronary lumen.…”
Section: Introductionmentioning
confidence: 99%